Curses in Aeschines’ Against Ctesiphon - Bajnok, Dániel (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
This paper examines the role of curse language in Aeschines’ Against Ctesiphon and argues that such vocabulary should not be understood as mere invective or metaphorical ornament. Terms such as γόης, μιαρός, and ἀλιτήριος, together with the invocation of the Amphictyonic oath, situate Demosthenes within the institutional logic of public conditional curses (arai). By associating him with ritually polluted persons and oath-breakers subject to divine destruction, Aeschines transforms forensic accusation into a form of civic and religious sanction. The speech thus demonstrates how curse discourse, rooted in oath and civic religion, functioned as a mechanism of political exclusion in fourth-century Athens.